Non-Fired Building Blocks Using Industrial Wastes (Journal of Engineering Science, 2022)
Bricks produced from traditional techniques and agricultural clay contribute considerably to the air pollutions in the world. Therefore, an urgent need to start using an environment-friendly alternative material/approach to save the fertile topsoil and conserve a clean environment. This research is aimed to produce non-fired bricks incorporating industrial solid waste from steel and power plants, including Fly ash and Ladle Furnace Slag (LFS), as a partial replacement of CEM I and lime. Induction Furnace Slag (IFS) is used as a partial/full replacement of natural fine aggregate (local sand) in the laboratory scale manufacturing process. The prepared building blocks conform to the minimum compressive strength requirement of 10.3 MPa per ASTM C62 and BDS 208 while the maximum compressive strength was 40.6 MPa. This highly promising performance pronounced the use of industrial waste materials in non-fired brick production to achieve a cleaner environment for a sustainable society.ournal of Engineering Science 12(3), 2021, 1-10